Effect of Nd-deficiency on electrochemical properties of NdBaCo2O6−δ cathode for intermediate-temperature solid oxide fuel cells. (29th June 2016) - Yi, Kaihua; Sun, Liping; Li, Qiang; Xia, Tian; Huo, Lihua; Zhao, Hui; Li, Jingwei; Lü, Zhe; Bassat, Jean-Marc; Rougier, Aline; Fourcade, Sébastien; Grenier, Jean-Claude
Abstract: Nd1− x BaCo2 O6−δ (N1− x BCO) is evaluated as cathode materials for intermediate-temperature solid oxide fuel cells (IT-SOFCs). The effects of Nd-deficiency on the crystal structure, thermal expansion behavior, electrical conductivity and electrochemical performance are studied. N1− x BCO oxides crystallize in the orthorhombic symmetry with Pmmm space group. A good chemical compatibility between N1− x BCO and CGO electrolyte is found at 1100 °C in air. Introducing Nd-deficiency promotes the formation of oxygen vacancy, and significantly improves the electrochemical performance of N1− x BCO cathodes. The lowest area specific resistance (ASR) value of 0.043 Ω cm 2 is obtained on the N0.96 BCO cathode at 700 °C in air. The rate limiting step for electrochemical oxygen reduction reaction (ORR) is charge transfer process at the interface. The power output of the electrolyte supported cell Ni-CGO/CGO/N0.96 BCO reaches 0.6 W cm −2 at 700 °C. Highlights: A-site Nd-deficiency double perovskite material Nd0.96 BaCo2 O6−δ was successfully prepared. Nd0.96 BaCo2 O6−δ exhibits superior cathode catalytic activity compared to the stoichiometric material NdBaCo2 O6−δ . The lowest area specific resistance is 0.043 Ω cm 2 at 700 °C. The reaction rate limiting step is identified as a charge transfer process.